Dichlorocarbene-Functionalized Fluorographene: Synthesis and Reaction Mechanism - Lazar, Petr; Chua, Chun Kiang; Holá, Kateřina; Zbořil, Radek; Otyepka, Michal; Pumera, Martin (Small (Weinheim an der Bergstrasse, Germany), 2015)
Halogen functionalization of graphene is an important branch of graphene research as it provides opportunities to tailor the band gap and catalytic properties of graphene. Monovalent C-X bond obviates pitfalls of functionalization with atoms of groups 13, 15, and 16, which can introduce various poorly defined groups. Here, the preparation of functionalized graphene containing both fluorine and chlorine atoms is shown. The starting material, fluorographite, undergoes a reaction with dichlorocarbene to provide dichlorocarbene-functionalized fluorographene (DCC-FG). The material is characterized by X-ray photoelectron spectroscopy, Raman spectroscopy, and high-resolution transmission electron microscopy with X-ray dispersive spectroscopy. It is found that the chlorine atoms in DCC-FG are distributed homogeneously over the entire area of the fluorographene sheet. Further density functional theory calculations show that the mechanism of dichlorocarbene attack on fluorographene sheet is a two-step process. Dichlorocarbene detaches fluorine atoms from fluorographene sheet and subsequently adds to the newly formed sp(2) carbons. Halogenated graphene consisting of two (or eventually three) types of halogen atoms is envisioned to find its way as new graphene materials with tailored properties.
Keywords: dichlorocarbene; DFT; graphene; functionalization; density functional theory; fluorographene